Aspectos sensoriais e físico-químicos de “iogurtes” de soja com espessantes/estabilizantes a base de fécula de inhame (Dioscorea alata), amido modificado e gelatina - Panhoni Manzano, Gabriela Paulino [UNESP]; Daiuto, Érica Regina [UNESP]; Janzantti, Natalia Soares [UNESP]; Rossi, Elizeu Antonio [UNESP] (Centro Pesquisa Processamento Alimentos, 2008)
This study had as objective to evaluate the effect of yam starch, modified starch from Cargill-Brasil (Amidomax 4800 (R)) and gelatin from Gelita-Brasil (GEL-LAC) as stabilizers/thickeners in different ratios and combinations in the soy yoghurt fermented with Enterococcus faecium and Lactobacillus helveticus ssp jugurti. Ten soy yoghurt formulations containing these different stabilizers/thickeners, always totalizing 0.5% in relation to the final formulation, were analyzed in sensorial and physical-chemical terms. Based on the observed results, it was concluded in relation to the sensorial point of view that the more appropriate product was processed only with gelatin at 0.5% concentration. This product also presented the best physical-chemical results related to consistency, syneresis and water holding capacity. However, the isolated use of gelatin increased fermentation time of the soy yoghurt.
Sensorial and physical-chemical aspects of soy yogurts with yam (Dioscorea Alata) starch, modified starch and gelatin as stabilizers/thickeners
Keywords: SOY YOGHURT; YAM; MODIFIED STARCH; GELATIN; SENSORIAL ANALYSIS; PHYSICAL-CHEMICAL ANALYSIS